Thymic output changes in children with clinical findings signaling a probable primary immunodeficiency - Neslihan Karaca; Elif Azarsız; Sanem Eren Akarcan; Güzide Aksu; Necil Kütükçüler (The Turkish Journal of Pediatrics)
Thymic maturation evaluation is inevitable for patients with clinical and laboratory findings for a primary immunodeficiency, as the T cellimmunodeficiencies are the most severe type. In this study, we aimed to show the usage of T cell surface molecule `CD31` for the evaluation of thymic output in patients (n: 66) with a large spectrum of findings signing a probable primary immunodeficiency. Besides the classical clinical and laboratory approach for these patients, T cell subpopulations as naive, memory, recent thymic emigrant cells were also investigated. The humoral immunodeficiency (34.8%), combined immunodeficiency (34.8%) and cardiopathy (7.6%) were the most frequent diagnosis groups. CD4+CD45RA+ naive T-cells percentages (p: 0.011) and absolute counts (p: 0.004) and absolute CD4+CD45RA+CD31+ RTE (recent thymic emigrant) cell counts (p: 0.007) were significantly lower in combined immunodeficiency group. Naive T-cells (p: 0.037) and RTE cells (p: 0.032) were also lower in patients who had cardiac surgery in the past. In conclusion, flow cytometric CD31+thymic naive RTE cell evaluation may provide rapid clinical information especially on T-cell immune dysfunction and CD4+CD45RA+CD31+ RTE cells may be used as an alternative to TRECs in the diagnosis of combined immunodeficiencies.